Energy-Dispersive X-ray (EDX) fluorescence based analysis of heavy metals in marble powder, paddy soil and rice (Oryza sativa L.) with potential health risks in District Malakand, Khyber Pakhtunkhwa, Pakistan. Issue 1 (1st January 2021) - Khan, Asghar; Khan, Muhammad Saleem; Hadi, Fazal; Saddiq, Ghulam; Khan, Abdul Naeem
ABSTRACT: Rice is staple food of Asian countries including Pakistan. Contamination of paddyfields with marble waste containing toxic metals has emerged as a key public health concern. Current study aimed to analyze heavy metal concentrations in marble powder, paddy soil and rice crop to estimate probable human health risks in District Malakand of Pakistan. Triplicate dry samples were analyzed through Energy Dispersive X-ray Fluorescence spectroscopy (ED-XRF). The marble waste increased the concentration of metals in paddy soil, subsequent increase in metals accumulation was found in rice grains. In grains the maximum concentration (mg/kg) of Fe (50.70), Cu (17.60), Mn (7.49) and Al (6.80) exceeded the permissible limits of FAO/WHO. The cumulative hazard index (HI) value from heavy metals through consumption of rice was greater than unity (HI > 1) indicating potential health risks. The results of Pearson correlation, Principal component analysis (PCA), and cluster analysis (CA) for metals were consistent.